Complexation with β-cyclodextrin derivatives enhanced the bioavailability of quercetin through improving solubility and inhibiting recrystallization - Qiao Chen; Hai-Xia Xu; Ji-Guang Chen; Lin Dai; Bao-Geng Fu; Qing-Feng Zhang (Journal of Food Engineering, 2027)

Sustained anaerobic valorization of refractory wastewater into bioenergy via abiotic-biotic hybrid systems: Unraveling synergistic hydrolysis and optimized interspecies electron transfer - Hui Xu; Shengqiang Hei; Guang Yang; Wanyi Fu; Xiaoyuan Zhang; Peng Liang; Bingcai Pan; Xia Huang (Journal of Environmental Sciences, 2026)

Laser pyrolysis of poly(methyl methacrylate) to high-yield and high-purity methyl methacrylate monomer: A solvent- and catalyst-free strategy for chemical recycling - Xu-Zhen Zhu; Guang-Jian He; Meng-Meng Wang; Fu-Lu Chang; Zi-Yang Hua; Hao-Bo Wang; Xuan-Qi Wu; Lun Chen (Chemical Engineering Journal, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Role of pectin degree of esterification in the structural assembly and oxidative stability of WPI–citrus Pectin–EGCG conjugates stabilized emulsion - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Food Hydrocolloids, 2026)

Near-infrared light-triggered nitric oxide-enhanced chemodynamic and photothermal therapy on magnesium alloy implants in osteosarcoma - Yongtang Wang; Lan Chen; Zhanfeng Zhou; Yuhan Liang; Tong Zhang; Rongbang Sun; Yueling Tian; Yang Liu; Yifu Fu; Huihan Wang; Guang Feng; Jianhua Miao; et al. (Chemical Engineering Journal, 2026)

Microscopic deformation mechanism of clay aggregates in view of the montmorillonite particles rearrangements under cyclic loading-unloading conditions - Zi-Yu Ding; Kai-Wen Tong; Yong-Gui Chen; Qiong Wang; Wen-Jie Dai; Xing-Guang Zhao; Chang-Fu Wei; Zhi-Jun Zhang (Applied Clay Science, 2026)

Radiocarbon Reveals Modern Carbon Exchange With Topsoil Inorganic Carbon in Drylands - Hui Wang; Jianbei Huang; Fernando T. Maestre; Guang Zhao; Nan Lu; Cong Wang; Weiliang Chen; De Shorn E. Bramble; Marion Schrumpf; Michaela A. Dippold; Yangjian Zhang; Sönke Zaehle; et al. (Global Change Biology, 2026)
Drylands store most of the global soil inorganic carbon (SIC), yet the extent to which this pool interacts with contemporary carbon (C) cycling remains poorly understood. To test whether SIC behaves primarily as an inert geological reservoir or instead bears a modern carbon imprint, we quantified SIC content and radiocarbon (∆ 14 C) at 42 dryland sites spanning broad aridity gradients across Eurasia. We also evaluated the climatic, edaphic, and biotic factors associated with variation in ∆ 14 C‐SIC. Across all sites, topsoil SIC (~0–10 cm) was strongly depleted in 14 C but consistently enriched relative to 14 C‐dead carbonates, indicating that it contains a measurable component derived from modern carbon inputs. In the Chinese drylands, ∆ 14 C‐SIC declined with increasing aridity, consistent with weaker modern carbon exchange under drier conditions and a greater contribution of inherited or 14 C‐depleted carbonate carbon. Soil pH and ∆ 14 C of soil organic carbon were the strongest predictors of ∆ 14 C‐SIC, suggesting that carbonate dissolution‐reprecipitation and the age of carbon entering soil CO 2 play key roles in determining SIC origins. At a subset of nine Chinese sites, ∆ 14 C‐SIC declined sharply with depth and approached 14 C‐dead values in subsoils, indicating little influence of modern carbon in deeper carbonate pools. The presence of mixed 14 C‐depleted and modern 14 C signatures in SIC potentially complicates the use of SIC isotopic signatures as proxies of environmental conditions. Together, our results indicate that dryland topsoil SIC commonly carries a measurable modern carbon signature that is tightly linked to contemporary carbon cycling. This coupling weakens with increasing aridity and soil depth, suggesting that environmental change in drylands may reshape one of the planet's largest carbon pools not only through changes in SIC stocks, but also through shifts in carbonate radiocarbon signatures and sources.

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

Semi-permeable membrane coverage accelerates composting through modulated bacterial succession and organic matter transformation - Fu-Sheng Sun; Chao Wang; Nader Mohamed; Lin Shi; Bo-Hao Yin; Yue-Bing Sun; Guang-Hui Yu (Waste Management, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Unveiling the dynamic electron transfer at asymmetric Fe-O-Co sites for sustained PMS activation via in-situ synchrotron spectroscopy - Xian-Chuan Chen; Fu-Sheng Sun; Cong-Qiang Liu; Guang-Hui Yu (Journal of Environmental Sciences, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Punicalagin alleviates enterotoxigenic Escherichia coli-induced intestinal mucosal injury via Krüppel-like factor 4 - Xiang-Guang Li; Xiaowen Zhao; Peizhi Zhu; Jibin Fu; Jiaxin Zhang; Zhixin Yu; Runting Chen; Mingxia Chen; Chuqiao Xiao; Junxia Zheng (Chemico-Biological Interactions, 2026)

Maximum mean discrepancy enhanced Informer for accurate cross-domain dual-timescale effluent prediction in wastewater treatment plants - Jun-Hong Zhou; Yang-Guang Xia; Xiao-Li Yang; Xin-Yi Xiang; Yu-Jia Fu (Bioresource Technology, 2026)

Leverage-based nutrient governance for drinking water sources using hydro-ecological zoning and source apportionment in the Yangtze River Basin - Haizhen Hu; Qing Fu; Sheng Chang; Yinying Zhu; Asaad Y. Shamseldin; Fan Zhang; Guang Yang; Chun Ye; Yueting Fan; Enrui Wang (Journal of Environmental Chemical Engineering, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Assessment of commercial NF membranes for selective separation of Mg2+/Li+ in simulated brines - Tian-tian Xue; Jian-wei Jia; Fan-xin Kong; Li-ping Yue; Guang-dong Sun; Jin-fu Chen (Journal of Water Process Engineering, 2026)

Flexural performance of a new transverse joint in hot-rolled steel section-UHPC composite deck under static and fatigue loads - Wenyong Cai; Xudong Shao; Junhui Cao; Xudong Zhao; Guang He; Panpan Li; Rusong Fu (Engineering Structures, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Gradient-structured PI/PDMS composites for photoactuation inspired by scallion leaf and bamboo node - Yue Fu; Zhenbang Li; Zitian Liu; Jiajun Yang; Song Zhao; Shuhui Kang; Guang Yang; Guang Liu; Liwen Zhang (Chemical Engineering Journal, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Association between environmental noise exposure during pregnancy and the risk of preterm birth: evidence from a multi-dimensional analysis - Guangjun Zheng; Yanyan Fu; Haofeng Zhang; Fudong He; Zhenger Fang; Biying Zhou; Xiu Qin; Lei Sun; Hua Xiao; Xi Fu; Guang Hao (Environmental Research, 2026)

Hydraulic retention time extension and multi-point reflux promote full-scale partial mainstream anaerobic ammonium oxidation (Anammox) at low temperatures - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Wen-Bo Liang; Yu-Jia Fu (Chemical Engineering Journal, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

Research on deep hidden mineralization favorable areas based on wide field electromagnetic datasets using generalized inverse inversion technology - Guang-di Liu; Hong-jun Tian; Yun-fu Zhu (Applied Geophysics, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Phototransformation of benzodiazepines in water mediated by dissolved black carbon: Mechanisms and the structure-reactivity relationship - Zhi-Cheng Zhou; Bin Yang; He-Yun Fu; Xiao-Lei Qu; Pei-Zhe Sun; Yong Feng; Guang-Guo Ying (Water Research, 2026)

Rational design of Whey protein–polysaccharide delivery systems: Synergistic mechanisms and advanced applications - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Trends in Food Science & Technology, 2026)

Nor-halimane and spiro-labdane diterpenoids with anti-inflammatory activity from Leucas ciliata Benth - Jia-Cai Kuang; Fu-Ling Cen; Xuan Zhang; Xu-Hua Nong; Xue-Ming Zhou; Xiao-Bao Li; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2026)

FeSe2 graphite intercalation compounds derived from spent graphite with spatial confinement effect enable high-performance sodium storage - Jiahao Yang; Chong Xu; Zizheng Zhou; Guang Ma; Shuang Liu; Dongyuan Zhang; Gong Cheng; Junjie Fu; Sai Che; Yan Jia; Yongfeng Li (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Characterization of the genetic architecture of adult plant resistance to sharp eyespot in Chinese wheat germplasm - Caiyun Liu; Wenling Zhai; Ningning Kang; Yanjiang He; Bisheng Fu; Wei Guo; Qiaofeng Zhang; Jin Cai; Ying Liu; Guang Qiu; Hua Jiang; Fujie Liu; et al. (Theoretical and Applied Genetics, 2026)

Research on Risk Evaluation of Tunnel Water Inrush Based on Multi-source Geophysical Exploration Data Fusion of MLP-Transformer Model - Guang Huo; Huai-bing Wang; Jin-gang Zhang; Yi-guo Xue; Bo-yin Fu; Fan-meng Kong; Zongwei Yan (Applied Geophysics, 2025)

One-step preparation of recyclable solid acid catalysts for biodiesel synthesis - Wenlong Miao; Guang Fu; Mingge Fu; Liuxin Xiang; Tian Wang; Thiquynhxuan Le; Libo Zhang; Phan Duc Lenh (Process Safety and Environmental Protection, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Applying natural product repurposing strategy to identify baicalein as novel caseinolytic protease P inhibitor and its application in the treatment of rice bacterial diseases - Zhaoju Sun; Teng Yang; Zhouqing Long; Xichun Fu; Jiao Meng; Xiang Zhou; Cai-Guang Yang; Song Yang (Pesticide Biochemistry and Physiology, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

A novel upcycling process of polystyrene wastes into benzaldehyde by catalyst-free laser flash depolymerization and in-line oxidation - Fu-Lu Chang; Lun Chen; Bin Hu; Fu-Rui Chen; Han Yang; Guang-Jian He (Chemical Engineering Journal, 2025)

A nine-year statistical study on the thunderstorms generated amid Dabie vortex background - Xue Xiao; Shen-Ming Fu; Bo Wang; Chao-Ying Yang; Shu-Guang Ning; Shi-Jun Sun; Kun-Shuang Zhu; Jian-Hua Sun (Atmospheric Research, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Numerical investigation and optimization of the cyclic construction method: A case study on steel-UHPC composite truss arches - Guang He; Xudong Shao; Junhui Cao; Panpan Li; Wenyong Cai; Rusong Fu (Engineering Structures, 2025)

One-pot synthesis of injectable freeze-dried platelet lysate functionalized peptides hydrogel for pressure ulcers repair - Kun Liu; Lei Wang; Dongdong Li; Fengying Qi; Shaoduo Yan; Xiaoyang Yi; Yanhong Li; Yuyuan Ma; Xian Su; Yuxin Zhang; Xunuo Li; Ruotong Zhang; et al. (Chemical Engineering Journal, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

A novel multifunctional self-assembled nanocellulose based scaffold for the healing of diabetic wounds - Guangrui Ma; Lina Fu; Hao Wang; Wenqi Yin; Pengyu He; Zhijun Shi; Guang Yang (Carbohydrate Polymers, 2025)

Meta‐Omics Analysis Reveals Global Distribution of Toxic Pseudo‐nitzschia and Enhanced Neurotoxin Production Under Climate Warming - Dong Xu; Zhuonan Wang; Georgina L. Brennan; Yuqiu Wei; Guanchao Zheng; Qingshan Luan; Xintong Huang; Yanmin Sun; Jia Yang; Xiaowen Zhang; Ke Sun; Xiao Fan; et al. (Global Change Biology, 2025)
The harmful diatom Pseudo‐nitzschia produces the neurotoxin domoic acid (DA), threatening human health and seafood safety in a changing climate. However, global patterns of Pseudo‐nitzschia abundance and the responses of DA production to underlying environmental drivers remain poorly understood, hindering accurate projections of their responses to environmental change. Using global meta‐omics data from Tara Oceans, alongside field survey data from the Chinese coasts and the Southern Ocean, we present the first evidence that four of the most toxic species— Pseudo‐nitzschia multiseries , Pseudo‐nitzschia multistriata , Pseudo‐nitzschia delicatissima , and Pseudo‐nitzschia pungens —are prevalent not only in coastal ecosystems but also in open ocean environments, spanning from pole to pole. We identify rising temperatures are recognized as a key driver of Pseudo‐nitzschia 's spatial distribution, DA production, and biosynthetic metabolism. Global models suggest that by 2100, under the SSP2‐4.5 climate scenario, the abundance of P. multiseries will increase by approximately 75.4%, while toxin production will be even more significantly enhanced, rising by up to 200.4%. This study significantly expands the known global distribution of these neurotoxin‐producing diatoms and predicts their increasing prevalence and toxicity under future global changes.

The Complete Mitochondrial Genome of Acrossocheilus spinifer (Osteichthyes: Cyprinidae) and Its Phylogenetic Analysis - Jian Gong; Shi-Qi She; Guang-Fu Liu; Xing-Xing Zhao; Le-Yang Yuan; E Zhang (Fishes, 2025)
In this study, we sequenced and characterized the complete mitochondrial genome of Acorssocheilus spinifer, an endemic stream-dwelling cyprinid species from South China first described in 2006. The mitogenome is 16,591 bp in length and contains the standard set of 37 genes (13 protein-coding genes, 22 tRNA genes, 2 rRNA genes) plus a control region. The genome exhibits typical cyprinid characteristics, with most genes encoded on the H-strand and a nucleotide composition biased toward A + T (55.9%). All tRNA genes display the typical cloverleaf secondary structure, except for tRNASer (GCU), which lacks the dihydrouridine (DHU) arm. Phylogenetic analysis using complete mitogenomes from 14 Acrossocheilus species revealed that 12 species form a monophyletic assemblage with three distinct clades. Within this framework, A. spinifer clusters closely with A. beijiangensis, supporting previous morphological observations. Our findings provide valuable genetic data for further taxonomic refinement and conservation efforts for Chinese barred species of Cyprinidae.

Synergistic bimolecular erosion-healing interfacial passivation for wide-bandgap perovskite and tandem solar cells - Shiqiang Fu; Guang Li; Shun Zhou; Jiahao Wang; Dexin Pu; Lishuai Huang; Zhiqiu Yu; Wanping Chen; Guojia Fang; Weijun Ke (Science Bulletin, 2025)

Simultaneous and instrument-free detection of quinine and crystal violet based on a dual-emissive Eu3+-functionalized metal-organic framework - Hou-Qun Yuan; Yuan Yuan; Si-Yi Liu; Jia-Hao Fu; Yi-Fan Xia; Wei Li; Meng-Yuan Pan; Lirong Jiang; Peiyao Chen; Guang-Ming Bao (Journal of Hazardous Materials, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

New maps of mafic mineral abundances in global mare units on the Moon - Yuzhen Wang; Haijun Cao; Jian Chen; Changqing Liu; Xuejin Lu; Chengxiang Yin; Xiaohui Fu; Le Qiao; Guang Zhang; Chengbao Liu; Peng Zhang; Zongcheng Ling (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Remotely estimate the cropland fractional vegetation cover using linear spectral mixture analysis and improved band operations - Yihan Yao; Jianing Shen; Jibo Yue; Yang Liu; Haikuan Feng; Meiyan Shu; Yuanyuan Fu; Hongbo Qiao; Tong Sun; Guang Zheng (International Journal of Remote Sensing, 2025)

Numerical study on wave–wind coupling effects on hydrodynamics and light capture performance of offshore multi-body floating photovoltaic system - Jia Fu; Yun-Peng Zhao; Guang-Chen Jia; Chao Ma; Jia-Qing Shu; Yan-Qian Sun (Ocean Engineering, 2025)

Assessment of the electrocoagulation coupled with E-peroxone for ultrafiltration fouling mitigation for shale gas produced water treatment - Shi-gang Chen; Guang-dong Sun; Fan-xin Kong; Yu-Xuan Chen; Jin-fu Chen (Journal of Environmental Chemical Engineering, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

The interplay of singlet oxygen and ABI4 in plant growth regulation - Zhong-Wei Zhang; Yu-Fan Fu; Guang-Deng Chen; Christiane Reinbothe; Steffen Reinbothe; Shu Yuan (Trends in Plant Science, 2025)

Laser flash pyrolysis of face mask waste to vinylidene-terminated PP wax and further functionalized as compatibilizer - Hao-Qin Zhang; Lun Chen; Chang-Qian Chen; Fu-Lu Chang; Yi-Xun Tian; Xia Jiang; Wei-Tao Huang; Bin Hu; Xian-Wu Cao; Xiao-Chun Yin; Guang-Jian He (Waste Management, 2025)

Efficient As(III) removal from acidic wastewater by polymorphism control of FeS - Jing Chen; Qingfeng Dong; Jing Li; Chaobo Zhang; Guang Fu; Zhanqing Lu (Journal of Water Process Engineering, 2025)

Visible-light excitable polymers with ultra-long phosphorescence afterglow achieved by boron-based dative bonds - Wei-Guang Chen; Yan-Fang Zhuang; Yan Wang; Zhi-Jian Chen; Yi-Fan Lv; Fu Song; Yu Chen (Chemical Engineering Journal, 2025)

Effect of Germination on Mineral Content Changes in Brown Rice (Oryza sativa L.) - Xiang Li; Chunmin Ma; Xin Bian; Yu Fu; Guang Zhang; Xiaofei Liu; Na Zhang (Biological Trace Element Research, 2025)

Biogeochemical process governing cadmium availability in sediments of typical coastal wetlands driven by drying-wetting alternation - Cheng-Cheng Jiang; Guang-Hui Yu; Xiao-Jie Zhou; Fu-Sheng Sun; Cong-Qiang Liu (Journal of Hazardous Materials, 2024)

A sensitive enzyme-free electrochemical sensor based on ZnWO4@co-MNPC@MIP for specific recognition and determination of chloramphenicol in milk sample - Mingcai Yao; Liang Dong; YuHang Fu; Haijun Li; Guang Luo (Food Chemistry, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Long-term changes of surface ozone and ozone sensitivity over the North China Plain based on 2015–2021 satellite retrievals - Chuanyong Zhu; Yichao Gai; Zhenguo Liu; Lei Sun; Siyuan Fu; Kun Liu; Leifeng Yang; Guang Pan; Baolin Wang; Chen Wang; Na Yang; Zhisheng Li; et al. (Air Quality, Atmosphere & Health, 2024)

Marine heatwaves alter competition between the cultured macroalga Gracilariopsis lemaneiformis and the harmful bloom alga Skeletonema costatum - Lin Gao; Yonglong Xiong; Fei-Xue Fu; David A. Hutchins; Kunshan Gao; Guang Gao (Science of The Total Environment, 2024)

MOF-801 enabled rapid-cycling atmospheric water harvester with vertically aligned photothermal channel - Mengyao Zhu; Guang He; Zongwei Wang; Junhao Chen; Xiang Fu; Huiyu Yang; Pei Lyu; Shaojin Gu; Xin Liu; Bin Shang (Journal of Environmental Chemical Engineering, 2024)

Cascade–Assembly–Confined Multilevel Supramolecular Assemblies for Multicolor Luminescence Information Storage and Cells Imaging Based on Slipped Pseudo[5]rotaxane - Hong–Guang Fu; Min Liu; Hui–Juan Wang; Xin–Xin Shi; Jing Xu (Chemical Engineering Journal, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

In-situ remediation of cadmium contamination in paddy fields: from rhizosphere soil to rice kernel - Hai Yan Long; Guang Fu Feng; Jun Fang (Environmental Geochemistry and Health, 2024)

Stereo visual-inertial localization algorithm for orchard robots based on point-line features - Xing Xu; Jinming Liang; Jianying Li; Guang Wu; Jieli Duan; Mohui Jin; Han Fu (Computers and Electronics in Agriculture, 2024)

Reclassification of Streptomyces violarus (Artamonova and Krassilnikov 1960) Pridham 1970 as a Later Heterotypic Synonym of Streptomyces violaceus (Rossi Doria 1891) Waksman 1953 using a Polyphasic Approach - Pei-Lan Long; Yin-Feng Wang; Li Fu; Yan Xiao; Shan-Guang Tang; Jian Gao (Current Microbiology, 2024)

Zircon U–Pb geochronology and geochemistry of Paleoproterozoic quartz monzonite in the Northern Yangtze Craton: Petrogenesis and geological implications - Wen-Xiang Zhang; Rui Li; Guang-Yan Zhou; Zhi-Fu Liu; Yuan-Bao Wu (Precambrian Research, 2024)

Evolution of morphology, structure, and performance of the COF membranes with monomer concentrations: Enabling effective desalination and kinetics analysis - Li-ping Yue; Fan-xin Kong; Yi Wang; Guang-dong Sun; Ai-guo Zhou; Jin-fu Chen (Desalination, 2024)

Prognostic model incorporating immune checkpoint genes to predict the immunotherapy efficacy for lung adenocarcinoma: a cohort study integrating machine learning algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Guang-Yu Wang; Fu-Quan Zhang (Immunologic Research, 2024)

Role of ginsenoside Rb1 in attenuating depression-like symptoms through astrocytic and microglial complement C3 pathway - Cheng-Fu Li; Qiu-Ping Zhang; Jie Cheng; Guang-Hui Xu; Ji-Xiao Zhu; Li-Tao Yi (Metabolic Brain Disease, 2024)

Saprobic Dothideomycetes from Yunnan, China: introducing a new species, Queenslandipenidiella lingcangensis , and a new host record for Periconia byssoides - Guang-Cong Ren; Er-Fu Yang; Jutamart Monkai; Kandawatte W. T. Chethana; Heng Gui; Antonio Roberto Gomes de Farias (New Zealand Journal of Botany, 2024)

Structurally diverse isoquinoline alkaloids from the barks of Alangium salviifolium (L. f.) Wangerin and their cytotoxicity - Yan-Mei Wei; Xuan Zhang; Fu-Ling Cen; Yi-Yi Du; Yuan-Ling Liu; Qiao-Yuan Han; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2024)

Floating MIL-88A(Fe)@expanded perlites catalyst for continuous photo-Fenton degradation toward tetracyclines under artificial light and real solar light - Guang-Chi Liu; Xiao-Hong Yi; Hong-Yu Chu; Chong-Chen Wang; Ya Gao; Fei Wang; Fu-Xue Wang; Peng Wang; Jian-Feng Wang (Journal of Hazardous Materials, 2024)

Numerical and experimental investigation of H2/CH4/Air combustion characteristics and thermal performance in the combustor with multi-bluff-body - Zhixin Huang; Qingguo Peng; Zhiwei Shi; Guang Fu; Huaqiang Xiao; Chaoqun Huang (Fuel, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Implementation of Viscoelastic Artificial Boundary and Seismic Motion Input Method in Three-Dimensional Discontinuous Deformation Analysis Method - Si-huang Lin; Tao Deng; Lu Zheng; Hong Zhang; Wei Wu; Xiao-dong Fu; Guang-qi Chen (Rock Mechanics and Rock Engineering, 2024)

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

Bicyclol mitigates lipopolysaccharide-induced acute lung injury through myeloid differentiation factor 88 inhibition - Lili Fu; Linting Cheng; Junliang Lu; Qianru Ye; Cong Shu; Chuchu Sun; Zhiguo Liu; Guang Liang; Weixin Zhao (Toxicology and Applied Pharmacology, 2024)

An antibacterial biologic patch based on bacterial cellulose for repair of infected hernias - Pengyu He; Dawei Wang; Ruizhu Zheng; Hao Wang; Lina Fu; Guoliang Tang; Zhijun Shi; Yiping Wu; Guang Yang (Carbohydrate Polymers, 2024)

Reactive Oxygen Species-Mediated Mitophagy and Cell Apoptosis are Involved in the Toxicity of Aluminum Chloride Exposure in GC-2spd - Hui- xin Peng; Fu Chai; Ke-heng Chen; Yan-xin Huang; Guang-ji Wei; Huixiong Yuan; Yan-fang Pang; Shi-hua Luo; Chun-fang Wang; Wen-cheng Chen (Biological Trace Element Research, 2024)

The impact of elevated CO2 concentration on photosynthesis, growth and hydraulics of evergreen and deciduous tree seedlings from a subtropical forest in Southwest China - Pei-Li Fu; Ya Zhang; Jin-Hua Qi; Yong-Jiang Zhang; Guang-You Hao; Patrick M. Finnegan; Qiao-Shun Yan; Ze-Xin Fan (Agricultural and Forest Meteorology, 2024)

Social determinants of health and their relation to suboptimal health status in the context of 3PM: a latent profile analysis - Lai Kun Tong; Yue Yi Li; Yong Bing Liu; Mu Rui Zheng; Guang Lei Fu; Mio Leng Au (EPMA Journal, 2024)

Recent development of carrier materials in anthocyanins encapsulation applications: A comprehensive literature review - Ze Fu; Hao Ju; Guang-Sen Xu; Yan-Chao Wu; Xiao Chen; Hui-Jing Li (Food Chemistry, 2024)

Predictive Model to Identify the Long Time Survivor in Patients with Glioblastoma: A Cohort Study Integrating Machine Learning Algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Yun-Long Sheng; Guang-Yu Wang; Fu-Quan Zhang; Xin Lian (Journal of Molecular Neuroscience, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Decolorization and detoxification of Brilliant Crocein GR by a newly enriched thermophilic consortium - Fang Tian; Guang Guo; Weilian Fu; Shiji Li; Keqiang Ding; Feng Yang; Chengyue Liang (Journal of Environmental Management, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Iron oxide–apatite deposits form from hydrosaline liquids exsolved from subvolcanic intrusions - Xin-Fu Zhao; Li-Ping Zeng; Wang Liao; Yi-Zhe Fan; Albert H. Hofstra; Poul Emsbo; Hao Hu; Guang Wen; Jian-Wei Li (Mineralium Deposita, 2024)

Heat-resistant lactic acid bacteria inoculants modulated the bacterial microbiota and fermentation quality of whole plant maize silage after long-term storage in the subtropical area - Guang-hao Xia; Ming-zhu Zhang; Yuan Huang; Chao Chen; Fu-yu Yang; Jun Hao (Animal Feed Science and Technology, 2024)

Hydraulic conductivity and microscopic properties of polyanionic cellulose and microscale zero-valent iron amended sand/bentonite backfills exposed to dichloromethane solution - Heng Zhuang; Guang-Yu Yang; Xian-Lei Fu; Zhe-Yuan Jiang; Yan-Jun Du (Science of The Total Environment, 2024)

Synergistic binding mechanisms of co-contaminants in soil profiles: Influence of iron-bearing minerals and microbial communities - Fu-Sheng Sun; Miao-Miao Wang; Xiang-Yang Zhao; Qiao-Yun Huang; Cong-Qiang Liu; Guang-Hui Yu (Environmental Pollution, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Functional connectivity changes of the hippocampal subregions in anti-N-methyl-D-aspartate receptor encephalitis - Yujie Yang; Shishun Fu; Guihua Jiang; Guang Xu; Junzhang Tian; Xiaofen Ma (Brain Imaging and Behavior, 2024)

Mono-2-ethylhexylphthalate (MEHP) is a potent agonist of human TRPA1 channel - Megan Goh; Lin Fu; Wei-Guang Seetoh; Ann Koay; Huang Hua; Shi Min Tan; Shermaine Huiping Tay; Elaine Chin Jinfeng; Nimo Abdullah; Shi Yan Ng; Manikandan Lakshmanan; Prakash Arumugam (Chemosphere, 2024)

Experimental investigation of blended H2/CH4 combustion in combustors with block for micro-thermophotovoltaic - Depeng Wei; Qingguo Peng; Hao Wang; Xinghua Tian; Huaqiang Xiao; Hui Liu; Guang Fu (Fuel, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Integrative application of biochar and arbuscular mycorrhizal fungi for enhanced chromium resistance in Medicago sativa - Jinglong Li; Gengxue Fu; Shuping Xing; Baodong Chen; Songlin Wu; Haiyan Feng; Guang Yang; Yaoyu Zhou; Xin Zhang (Science of The Total Environment, 2023)

Multiple paternally inherited chloroplast capture events associated with Taxus speciation in the Hengduan Mountains - Han-Tao Qin; Michael Mӧller; Richard Milne; Ya-Huang Luo; Guang-Fu Zhu; De-Zhu Li; Jie Liu; Lian-Ming Gao (Molecular Phylogenetics and Evolution, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Investigation on H2/CH4 blended combustion in a micro-tube with dual-inlet at varied operating conditions - Depeng Wei; Zhiwei Shi; Qingguo Peng; Jia Wei; Hao Wang; Xinghua Tian; Zhixin Huang; Huaqiang Xiao; Yaojie Tu; Guang Fu (Fuel, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Enterochromaffin Cell: Friend or Foe for Human Health? - Yang Yu; Yong-Chang Li; Fu-Chao Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2023)

Visible-light-induced photocatalytic CO2 reduction over zirconium metal organic frameworks modified with different functional groups - Yuexian Du; Guang'an Jie; Huilin Jia; Jiahui Liu; Jieyu Wu; Yanghe Fu; Fumin Zhang; Weidong Zhu; Maohong Fan (Journal of Environmental Sciences, 2023)

Seasonal variation characteristics of atmospheric peroxyacetyl nitrate (PAN) and its source apportionment in a megacity in southern China - Shi-Yong Xia; Xiao-Feng Huang; Zhi-Jie Li; Nan Fu; Zhen Jiang; Li-Ming Cao; Le-Wei Zeng; Guang-He Yu (Science of The Total Environment, 2023)

A versatile organic silicate aluminum hybrid coagulant for broad-spectrum removal of heavy metal ions - Jin-Wei Liu; Tao Fu; Guang-Dong Sun; Xiao-Ran Shen; Sheng Liu; Yang He; Yi Xu; Hua-Zhang Zhao (Chemical Engineering Journal, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Response of soil fungal community to chromium contamination in agricultural soils with different physicochemical properties - Chuning Ji; Jiu Huang; Xuemeng Zhang; Guang Yang; Shuping Xing; Wei Fu; Zhipeng Hao; Baodong Chen; Xin Zhang (Science of The Total Environment, 2023)

Anthraquinones with potential antiproliferative activities from the fruits of Morinda citrifolia - Zhang-Yang Shen; Ying-Ying Zhao; Ze-Hua Qiao; Zhen Xie; Ruo-Qing Guan; Ze-Yu Liu; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2023)

Investigation of CH4 and porous media addition on thermal and working performance in premixed H2/air combustion for micro thermophotovoltaic - Bo Xie; Qingguo Peng; Zhiwei Shi; Jia Wei; Zhuang Kang; Depeng Wei; Xinghua Tian; Guang Fu (Fuel, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Protein engineering of invertase for enhancing yeast dough fermentation under high-sucrose conditions - Yijin Zhao; Kaiwen Meng; Jinyu Fu; Shijie Xu; Guang Cai; Geng Meng; Jens Nielsen; Zihe Liu; Yueping Zhang (Folia Microbiologica, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Strategies for improving the photocatalytic performance of metal-organic frameworks for CO2 reduction: A review - Ke Guo; Ijaz Hussain; Guang′an Jie; Yanghe Fu; Fumin Zhang; Weidong Zhu (Journal of Environmental Sciences, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

The effect of nitrite and nitrate treatment on growth performance, nutritional composition and flavor-associated metabolites of grass carp (Ctenopharyngodon idella) - Jun-Ming Zhang; Bing Fu; Yi-chao Li; Jin-Hui Sun; Jun Xie; Guang-Jun Wang; Jing-Jing Tian; Gen Kaneko; Er-Meng Yu (Aquaculture, 2023)

Mechanism, performance and modification methods for NH3-SCR catalysts: A review - Zhiwei Shi; Qingguo Peng; Jiaqiang E; Bo Xie; Jia Wei; Ruixue Yin; Guang Fu (Fuel, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Seismic performance and reinforcement strategy of frame infilled with ESPS block masonry wall: experimental, theoretical and numerical investigation - Biao Liu; Guo-Liang Bai; Guang-Ming Fu (Bulletin of Earthquake Engineering, 2022)

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

Phenomenon of the sediment deposition in a hydraulic jump region of open channels - Wei-lin Xu; Guo-guang Wang; Shi-hao Fu; Wang-ru Wei (Journal of Mountain Science, 2022)

Bioenergy Production Potential of 16 Energy Crops on Marginal Land in China - Tongcheng Fu; Yi Xu; Meng Li; Shuai Xue; Zengqiang Duan; Guang Hui Xie (BioEnergy Research, 2022)

Haze management: is urban public transportation priority effective? - Ziyu Zhai; Xiaoling Fu; Ming Yi; Mingyue Sheng; Fengtao Guang (Environmental Science and Pollution Research, 2022)

Reduced left lateralized functional connectivity of the thalamic subregions between short-term and chronic insomnia disorder - Xiaofen Ma; Shishun Fu; Guang Xu; Mengchen Liu; Yikai Xu; Guihua Jiang; Junzhang Tian (Sleep and Biological Rhythms, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Recent advances in tissue stem cells - Xin Fu; Qiang He; Yu Tao; Mengdi Wang; Wei Wang; Yalong Wang; Qing Cissy Yu; Fang Zhang; Xiaoyu Zhang; Ye-Guang Chen; Dong Gao; Ping Hu; et al. (Science China Life Sciences, 2021)

New phenolic acids from the whole herb of Elephantopus scaber Linn. and their anti-inflammatory activity - Lu Fu; Di Pei; Meng Yu; Hai Shang; Jin-Guang Si; Hong-Wu Zhang; Tao Zhang; Zhong-Mei Zou (Natural Product Research, 2021)

Hydrological characteristics and changes in the Nu-Salween River basin revealed with model-based reconstructed data - Fan Yang; Hui Lu; Kun Yang; Guang-wei Huang; Yi-shan Li; Wei Wang; Ping Lu; Fu-qiang Tian; Yu-gang Huang (Journal of Mountain Science, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

A Numerical Meso-Scale Elasto-Plastic Damage Model for Modeling the Deformation and Fracturing of Sandstone Under Cyclic Loading - Tao Xu; Meng Fu; Sheng-qi Yang; Michael J. Heap; Guang-lei Zhou (Rock Mechanics and Rock Engineering, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Budgets of rotational and divergent kinetic energy in the warm-sector torrential rains over South China: a case study - Shui-Xin Zhong; Wei-Guang Meng; Fu-You Tian (Meteorology and Atmospheric Physics, 2021)
The contributions of divergent and rotational wind components to the kinetic energy budget during a record-breaking rainstorm on 7 May 2017 over South China are examined. This warm-sector extreme precipitation caused historical maximum of 382.6 mm accumulated rainfall in 3 h over the Pearl River Delta (PRD) regions in South China. Results show that there was a high low-level southerly wind-speed tongue stretching into the PRD regions from the northeast of the South China Sea (SCS) during this extreme precipitation. The velocity potential exhibited a low-value center as well as a low-level divergence-center over the SCS. The rotational components of the kinetic energy (KR)-related terms were the main contribution-terms of the kinetic energy budget. The main contribution-terms of KR and the divergent component of kinetic energy (KD) were the barotropical and baroclinic processes-related terms due to cross-contour flow and the vertical flux divergence.

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

3D inversion of audio-magnetotelluric data for mineral exploration: A case study of Layikeleke buried porphyry copper deposit, Xinjiang, China - Fu Guang-Ming; Yan Jia-Yong; Chen Hui; Meng Gui-Xiang; Yu Hui; Luo Fan; Luo Lei; Tao Xin (Applied Geophysics, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Bioactive Eudesmane sesquiterpenes from Artabotrys hongkongensis Hance - Qing Wen; Yan-Ping Liu; Gui Yan; Shuo Yang; Shi Hu; Jing Hua; Wen-Qing Yin; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2020)

Photoprotection capacity of microalgae improved by regulating the antenna size of light-harvesting complexes - Guang-Rong Hu; Yong Fan; Yan-Lin Zheng; Feng Xu; Lei Zhang; Fu-Li Li (Journal of Applied Phycology, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Short hairpin RNAs targeting M and N genes reduce replication of porcine deltacoronavirus in ST cells - Wen-yuan Gu; Yan Li; Bao-jing Liu; Jing Wang; Guang-fu Yuan; Shao-jie Chen; Yu-Zhu Zuo; Jing-Hui Fan (Virus Genes, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Selection signatures of litter size in Dazu black goats based on a whole genome sequencing mixed pools strategy - Guang-Xin E; Yong-Ju Zhao; Yong-Fu Huang (Molecular Biology Reports, 2019)

Seroprevalence of porcine bocavirus in pigs in north-central China using a recombinant-NP1-protein-based indirect ELISA - Qian-Kai Shi; Jian-Lou Zhang; Wen-Yuan Gu; Lin-Shan Hou; Guang-Fu Yuan; Shao-Jie Chen; Jing-Hui Fan; Yu-Zhu Zuo (Archives of Virology, 2019)

Biologically active oligostilbenes from the stems of Vatica mangachapoi and chemotaxonomic significance - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Identification, evolution and alternative splicing profile analysis of the splicing factor 30 (SPF30) in plant species - Di Zhang; Jing-Fang Yang; Bei Gao; Tie-Yuan Liu; Ge-Fei Hao; Guang-Fu Yang; Li-Jun Fu; Mo-Xian Chen; Jianhua Zhang (Planta, 2019)

A new morphinandienone alkaloid from the stems of Fissistigma tungfangense - Qi Zhou; Yan-Hui Fu; Yu-Qin Zhang; Shou-Yuan Wu; Xiao-Ping Song; Wei Xu; Guang-Ying Chen (Natural Product Research, 2019)

Genome-wide identification and functional analysis of the splicing component SYF2/NTC31/p29 across different plant species - Yuan Tian; Mo-Xian Chen; Jing-Fang Yang; H. H. K. Achala; Bei Gao; Ge-Fei Hao; Guang-Fu Yang; Zhi-Yong Dian; Qi-Juan Hu; Di Zhang; Jianhua Zhang; Ying-Gao Liu (Planta, 2019)

Current genetic diversity in eight local Chinese sheep populations - Guang-Xin E; Yue-Hui Ma; Ming-Xing Chu; Qiong-Hua Hong; Yong-Fu Huang (Molecular Biology Reports, 2019)

Protective effects of protopanaxatriol on acute liver injury induced by concanavalin A - Lina Jin; Xue Fu; Shuangshuang Yao; Jian Yang; Guang Ning; Zhiguo Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Synchronously enhancing biogas production, sludge reduction, biogas desulfurization, and digestate treatment in sludge anaerobic digestion by adding K2FeO4 - Shuli Liu; Guang Yang; Jinwei Fu; Guangming Zhang (Environmental Science and Pollution Research, 2018)

Total and available metal concentrations in soils from six long-term fertilization sites across China - Dong-Xing Guan; Fu-Sheng Sun; Guang-Hui Yu; Matthew L. Polizzotto; Yun-Gen Liu (Environmental Science and Pollution Research, 2018)

Age and nature of the Jurassic–Early Cretaceous mafic and ultramafic rocks from the Yilashan area, Bangong–Nujiang suture zone, central Tibet: implications for petrogenesis and tectonic Evolution - Yun Zhong; Xi-Chong Hu; Wei-Liang Liu; Bin Xia; Xiao Zhang; Wei Huang; Yuan-Bin Fu; Yu-Guang Wang (International Geology Review, 2018)

A new polyoxygenated cyclohexene derivative from Artabotrys hainanensis - Jin-Ying Tang; Yan-Ping Liu; Peng-Kun Ju; Xiu-Lan Luo; Zhi-Jie Zhang; Peng Ren; Liang Lai; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2018)

Haploid plant regeneration from hardy kiwifruit (Actinidia arguta Planch.) anther culture - Guang-Fu Wang; Hong-Yan Qin; Dan Sun; Shu-Tian Fan; Yi-Ming Yang; Zhen-Xing Wang; Pei-Llei Xu; Ying Zhao; Ying-Xue Liu; Jun Ai (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Effect of Plant Density on Sweet and Biomass Sorghum Production on Semiarid Marginal Land - Chaochen Tang; Chuandong Sun; Fu Du; Feng Chen; Asif Ameen; Tongcheng Fu; Guang Hui Xie (Sugar Tech, 2018)

Detoxification of aflatoxins on prospective approach: effect on structural, mechanical, and optical properties under pressures - Yong-Kai Wei; Xiao-Miao Zhao; Meng-Meng Li; Jing-Xin Yu; Selvaraj Gurudeeban; Yan-Fei Hu; Guang-Fu Ji; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

A new dihydrochalcone glycoside from the stems of Homalium stenophyllum - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2018)

Ammonium, nitrate, and urea play different roles for lipid accumulation in the nervonic acid—producing microalgae Mychonastes afer HSO-3-1 - Cheng Yuan; Kai Xu; Juan Sun; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2018)

Gcn5‐dependent histone H3 acetylation and gene activity is required for the asexual development and virulence of Beauveria bassiana - Qing Cai; Juan‐Juan Wang; Bo Fu; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2018)
Summary Gcn5 is a core histone acetyltransferase that catalyzes histone H3 acetylation on N‐terminal lysine residues in yeasts and was reported to catalyze H3K9/K14 acetylation required for activating asexual development in Aspergillus . Here, we report a localization of Gcn5 ortholog in the nucleus and cytoplasm of Beauveria bassiana , a fungal insect pathogen. Deletion of gcn5 led to hypoacetylated H3 at K9/14/18/27 and 97% reduction in conidiation capacity as well as severe defects in colony growth and conidial thermotolerance. Two master conidiation genes, namely brlA and abaA , were transcriptionally repressed to undetectable level in Δ gcn5 , but sharply upregulated in wild‐type, at the beginning time of conidiation. Based on chromatin immunoprecipitation, both DNA and acetylation levels of the distal and proximal fragments of the brlA promoter bound by acetylated H3K14 alone were upregulated in wild‐type, but not in Δ gcn5 , at the mentioned time. In Δ gcn5 , normal cuticle infection was abolished while virulence through cuticle‐bypassing infection was greatly attenuated, accompanied by drastically reduced activities of putative cuticle‐degrading enzymes, retarded dimorphic transition and transcriptional repression of associated genes. These findings unveil a novel mechanism by which Gcn5 activates asexual development pathway by acetylating H3K14 and regulates the virulence‐related cellular events in B. bassiana .

Revealing histological and morphological features of female reproductive system in tree shrew (Tupaia belangeri) - Shan Zhong; Shi-yao Zhang; Hui-jie Xing; Xiao-tan Zhang; Guang Wang; Yong-ping Bao; Jiang-nan Fu; Xuesong Yang (Zoomorphology, 2018)

Effect of Sevoflurane Anesthesia on Brain Is Mediated by lncRNA HOTAIR - Jian-yue Wang; Yong Feng; Yan-hong Fu; Guang-li Liu (Journal of Molecular Neuroscience, 2018)

A new isoflavone from the roots of Ficus auriculata - Cui-Cui Qi; Yan-Hui Fu; Wen-Hao Chen; Guang-Ying Chen; Chun-Yan Dai; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

A new wortmannine derivative from a Tripterygium wilfordii endophytic fungus Talaromyces wortmannii LGT-4 - Jing-Yun Sun; Zhong-Duo Yang; Guang-Chao Fu; Yong-Gang Wang; Hong-Yan Xue; Zong-Mei Shu (Natural Product Research, 2017)

C5a/C5aR Pathway Plays a Vital Role in Brain Inflammatory Injury via Initiating Fgl-2 in Intracerebral Hemorrhage - Bangqing Yuan; Fenlan Fu; Shaokuan Huang; Chuangan Lin; Guang Yang; Kunlong Ma; Hui Shi; Zhao Yang (Molecular Neurobiology, 2017)

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Soil detachment and transport under the combined action of rainfall and runoff energy on shallow overland flow - Guang-lu Li; Teng-hui Zheng; Yu Fu; Bai-qiao Li; Teng Zhang (Journal of Mountain Science, 2017)

Plant-soil feedback contributes to intercropping overyielding by reducing the negative effect of take-all on wheat and compensating the growth of faba bean - Guang Zhou Wang; Hai Gang Li; Peter Christie; Fu Suo Zhang; Jun Ling Zhang; James D. Bever (Plant and Soil, 2017)

IR Spectra of Different O2-Content Hemoglobin from Computational Study: Promising Detector of Hemoglobin Variant in Medical Diagnosis - Su-qin Zhou; Tu-nan Chen; Guang-fu Ji; En-ren Wang (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Biomass Yield and Nutrient Uptake of Energy Sorghum in Response to Nitrogen Fertilizer Rate on Marginal Land in a Semi-Arid Region - Asif Ameen; Xiaolin Yang; Feng Chen; Chaochen Tang; Fu Du; Shah Fahad; Guang Hui Xie (BioEnergy Research, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

Analysis of Gateroad Stability in Relation to Yield Pillar Size: A Case Study - Guang-chao Zhang; Fu-lian He; Hong-guo Jia; Yong-hui Lai (Rock Mechanics and Rock Engineering, 2017)

Perfluoroalkyl substances with isomer analysis in umbilical cord serum in China - Ya-Zhi Zhang; Xiao-Wen Zeng; Zhengmin Qian; Michael G. Vaughn; Sarah Dee Geiger; Li-Wen Hu; Long Lu; Chuanxi Fu; Guang-Hui Dong (Environmental Science and Pollution Research, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Life Cycle Analysis of Greenhouse Gas and PM2.5 Emissions from Restaurant Waste Oil Used for Biodiesel Production in China - Yang Yang; Tongcheng Fu; Weiqing Bao; Guang Hui Xie (BioEnergy Research, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

The far-upstream regulatory region of RFL is required for its precise spatial-temporal expression for floral development in rice - Sulin Lou; Shuifu Chen; Xiucai Zhao; Letian Chen; Jian Zhang; Hongxiang Fu; Yao-Guang Liu; Yuanling Chen (Plant Molecular Biology, 2017)

Haplotype of platelet receptor P2RY12 gene is associated with residual clopidogrel on-treatment platelet reactivity - Xiao-yan Nie; Jun-lei Li; Yong Zhang; Yang Xu; Xue-li Yang; Yu Fu; Guang-kai Liang; Yun Lu; Jian Liu; Lu-wen Shi (Journal of Zhejiang University-SCIENCE B, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

The effects of starvation and re-feeding on growth and swimming performance of juvenile black carp (Mylopharyngodon piceus) - Xu Pang; Shi-Jian Fu; Xiu-Ming Li; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2016)

Two new compounds, deacetylisowortmins A and B, isolated from an endophytic Fungus, Talaromyces wortmannii LGT-4 - Guang-Chao Fu; Zhong-Duo Yang; Shuang-Yan Zhou; Hai-Tao Yu; Fei Zhang; Xiao-Jun Yao (Natural Product Research, 2016)

Degradation of litter quality and decline of soil nitrogen mineralization after moso bamboo (Phyllostachys pubscens) expansion to neighboring broadleaved forest in subtropical China - Qing-ni Song; Ming Ouyang; Qing-pei Yang; Hui Lu; Guang-yao Yang; Fu-sheng Chen; Jian-Min Shi (Plant and Soil, 2016)

The adipokine Chemerin induces lipolysis and adipogenesis in bovine intramuscular adipocytes - Yuan-Yuan Fu; Kun-Lin Chen; Hui-Xia Li; Guang-Hong Zhou (Molecular and Cellular Biochemistry, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Effect of Lactobacillus Strains on Intestinal Microflora and Mucosa Immunity in Escherichia coli O157:H7-Induced Diarrhea in Mice - Xin Bian; Ting-ting Wang; Min Xu; Smith Etareri Evivie; Guang-Wen Luo; Hong-zhang Liang; Shang-fu Yu; Gui-Cheng Huo (Current Microbiology, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

A new kaurane diterpenoid from Isodon inflexus - Guang-Hua Xu; Xing-Fu Cai; Xuejun Jin; Jung Joon Lee (Natural Product Research, 2016)

Palaeoproterozoic A-type magmatism in northern Wuyishan terrane, Southeast China: petrogenesis and tectonic implications - Zhi-Hong Chen; Guang-Fu Xing; Xi-Lin Zhao (International Geology Review, 2016)

Sunfleck limits the small-scale distribution of endangered Kingdonia uniflora in the natural habitat of subalpine forest proved by its photosynthesis - Chen-Guang Zhang; Xiao Liu; Yi-Lei Fan; Mao Wang; Yong-Fu Chai; Peng-Cheng Wan; Ya-Min Wang; Ming Yue (Acta Physiologiae Plantarum, 2016)

Cloning and Characterization of a Pyruvate Carboxylase Gene from Penicillium rubens and Overexpression of the Genein the Yeast Yarrowia lipolytica for Enhanced Citric Acid Production - Ge-Yi Fu; Yi Lu; Zhe Chi; Guang-Lei Liu; Shou-Feng Zhao; Hong Jiang; Zhen-Ming Chi (Marine Biotechnology, 2016)

Photodegradation of Mefenamic Acid in Aqueous Media: Kinetics, Toxicity and Photolysis Products - Ping Chen; Feng Liang Wang; Kun Yao; Jing Shuai Ma; Fu Hua Li; Wen Ying Lv; Guo Guang Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

Spatial analysis of meteorological drought return periods in China using Copulas - Xiong-Fei Liu; Shi-Xin Wang; Yi Zhou; Fu-Tao Wang; Guang Yang; Wen-Liang Liu (Natural Hazards, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

Distribution and phylogenetic analysis of Culex flavivirus in mosquitoes in China - Wenkai Liang; Xiaoxia He; Guifang Liu; Shaobai Zhang; Shihong Fu; Min Wang; Weixin Chen; Ying He; Xiaoyan Tao; Hongyue Jiang; Xiaojuan Lin; Xiaoyan Gao; et al. (Archives of Virology, 2015)

Metabolic engineering of 2-phenylethanol pathway producing fragrance chemical and reducing lignin in Arabidopsis - Guang Qi; Dian Wang; Li Yu; Xianfeng Tang; Guohua Chai; Guo He; Wenxuan Ma; Shengying Li; Yingzhen Kong; Chunxiang Fu; Gongke Zhou (Plant Cell Reports, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Photodegradation of Ibuprofen Under UV–Vis Irradiation: Mechanism and Toxicity of Photolysis Products - Fu Hua Li; Kun Yao; Wen Ying Lv; Guo Guang Liu; Ping Chen; Hao Ping Huang; Ya Pu Kang (Bulletin of Environmental Contamination and Toxicology, 2015)

SEM+: tool for discovering concept mapping in Earth science related domain - Jin Guang Zheng; Linyun Fu; Xiaogang Ma; Peter Fox (Earth Science Informatics, 2015)

The effect of temperature on repeat swimming performance in juvenile qingbo (Spinibarbus sinensis) - Xu Pang; Xing-Zhong Yuan; Zhen-Dong Cao; Yao-Guang Zhang; Shi-Jian Fu (Fish Physiology and Biochemistry, 2015)

Effect of different sulfides on cadmium distribution during sludge combustion based on experimental and thermodynamic calculation approaches - Jing-Yong Liu; Jie-Wen Fu; Shui-Yu Sun; Xun-An Ning; Yu-Jie Wang; Tao Chen; Guang-Qian Luo; Wu-Ming Xie; Zuo-Yi Yang; Zhong-Xu Zhuo (Environmental Science and Pollution Research, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Molecular cloning and expression analysis of 13 NAC transcription factors in Miscanthus lutarioriparius - Lu Ji; Ruibo Hu; Jianxiong Jiang; Guang Qi; Xuanwen Yang; Ming Zhu; Chunxiang Fu; Gongke Zhou; Zili Yi (Plant Cell Reports, 2014)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Assessing scalar concentration footprint climatology and land surface impacts on tall-tower CO2 concentration measurements in the boreal forest of central Saskatchewan, Canada - Baozhang Chen; Huifang Zhang; Nicholas C. Coops; Dongjie Fu; Douglas E. J. Worthy; Guang Xu; T. Andy Black (Theoretical and Applied Climatology, 2014)

Acutissimanide, a new lignan with antioxidant activity isolated from the bark of Quercus acutissima Carruth - Xiao-Li Zeng; Guang-Miao Fu; Kai Tian; Jing-Xian Sun; Hua-Bin Xiong; Xiang-Zhong Huang; Zhi-Yong Jiang (Natural Product Research, 2014)

Conceptual study of lunar-based SAR for global change monitoring - HuaDong Guo; YiXing Ding; Guang Liu; DaoWei Zhang; WenXue Fu; Lu Zhang (Science China Earth Sciences, 2014)

Co-delivery of Dexamethasone and Green Tea Polyphenols Using Electrospun Ultrafine Fibers for Effective Treatment of Keloid - Jinrong Li; Rong Fu; Long Li; Guang Yang; Shan Ding; Zhendong Zhong; Shaobing Zhou (Pharmaceutical Research, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Cell wall polysaccharide distribution in Miscanthus lutarioriparius stem using immuno-detection - Yingping Cao; Junling Li; Li Yu; Guohua Chai; Guo He; Ruibo Hu; Guang Qi; Yingzhen Kong; Chunxiang Fu; Gongke Zhou (Plant Cell Reports, 2014)

Physiological and morphological responses to the first bout of refeeding in southern catfish (Silurus meridionalis) - Ling-Qing Zeng; Shi-Jian Fu; Xiu-Ming Li; Feng-Jie Li; Bin Li; Zhen-Dong Cao; Yao-Guang Zhang (Journal of Comparative Physiology B, 2014)

Occurrence and removal of six pharmaceuticals and personal care products in a wastewater treatment plant employing anaerobic/anoxic/aerobic and UV processes in Shanghai, China - Dan Wang; Qian Sui; Shu-Guang Lu; Wen-Tao Zhao; Zhao-Fu Qiu; Zhou-Wei Miao; Gang Yu (Environmental Science and Pollution Research, 2014)

Research on global change scientific satellites - HuaDong Guo; WenXue Fu; XinWu Li; Pei Chen; Guang Liu; Zhen Li; Cheng Wang; Qing Dong; LiPing Lei; LinYan Bai; QingJie Liu (Science China Earth Sciences, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Verapamil Reverses Myocardial No-Reflow After Primary Percutaneous Coronary Intervention in Patients with Acute Myocardial Infarction - Qiang Fu; Wen Lu; Yi-jie Huang; Qiang Wu; Lin-guang Wang; Hai-bo Wang; Shu-zhong Jiang; Yan-jiong Wang (Cell Biochemistry and Biophysics, 2013)

The Effect of Deposition Se on the mRNA Expression Levels of GPxs in Goats from a Se-enriched County of China - Lei Zhang; Zhan-qin Zhou; Guang Li; Ming-zhe Fu (Biological Trace Element Research, 2013)

Petrogenesis of a Palaeoproterozoic S-type granite, central Wuyishan terrane, SE China: implications for early crustal evolution of the Cathaysia Block - Zhi-Hong Chen; Guang-Fu Xing (International Geology Review, 2013)

Development of rRNA-targeted probes for detection of Prorocentrum micans (Dinophyceae) using whole cell in situ hybridization - Guo Fu Chen; Yang Liu; Chun Yun Zhang; Chao Shuai Ma; Bao Yu Zhang; Guang Ce Wang; Zhong Xu; Dou Ding Lu (Journal of Applied Phycology, 2013)

3,3-Dimethyl-1-butanol, a parakairomone component to Aleurodicus dispersus (Hemiptera: Aleyrodidae) - Li-Xia Zheng; Wei-Jian Wu; Guang-Wen Liang; Yue-Guan Fu (Arthropod-Plant Interactions, 2013)

Separation of mandelic acid and its derivatives with new immobilized cellulose chiral stationary phase - Jie Zhou; Qian Liu; Guang-jun Fu; Zhen-zhong Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Early Middle Triassic mafic dikes from the Baoshan subterrane, western Yunnan: implications for the tectonic evolution of the Palaeo-Tethys in Southeast Asia - Shi-Yong Liao; Fu-Guang Yin; Zhi-Ming Sun; Dong-Bing Wang; Yuan Tang; Jie Sun (International Geology Review, 2013)

Germination of phytoplankton resting cells from surface sediments in two areas of the S outhern C hinese coastal waters - Zhao‐Hui Wang; Yong‐Hu Fu; Wei Kang; Ju‐Fang Liang; Yang‐Guang Gu; Xiao‐Liang Jiang (Marine Ecology, 2013)
To understand the role of phytoplankton resting cells in the outbreak of algal blooms, particularly harmful algal blooms, surface sediments were collected monthly from A pril 2007 to M arch 2008 from two bays near the international ports in the S outhern C hinese coastal waters. Sieved sediments were incubated for 20 and 40 days, and germinated vegetative cells were observed. Altogether, 97 taxa were recorded, of which 50 were diatoms and 35 dinoflagellates. Vegetative cells of cyanobacteria, chlorophytes, dictyophytes, euglenophytes, haptophytes, and raphidophytes were also observed. Centric diatoms such as C haetoceros , M elosira , S keletonema , and T halassiosira dominated. S crippsiella , G ymnodinium , and A lexandrium were common dinoflagellate taxa. Diatom spores germinated in samples from all seasons but were abundant in the autumn and winter samples. Low numbers of dinoflagellate cells germinated in the winter samples. The nanophytoplankton taxa, G ymnodinium corii and C hrysochromulina sp., which have not been recorded in the previous phytoplankton surveys, were abundant, suggesting either their new appearance in the water column or perhaps that they were overlooked in routine phytoplankton monitoring due to their small sizes. Vegetative cells of harmful or potentially harmful taxa were germinated, and some of them such as A mphidinium , G ambierdiscus , O streopsis , and C oolia have not previously been reported in the study area. Based on the results of the incubation of sediments from the two bays near the international ports, it is suggested that international shipping increases the risk of the introduction of new phytoplankton species and thus promotes the incidence of harmful algal blooms.

Pedobacter hainanensis sp. nov., Isolated from Seaside Soil - Yan-yu Meng; Yun-bin Fu; Meng-yu Wang; Yong Zhao; Qi-shun Liu; Yu-guang Du (Current Microbiology, 2013)

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

A Novel Endogenous Induction of ColE7 Expression in a csrA Mutant of Escherichia coli - Hao-Wei Chang; Tsung-Yeh Yang; Guang-Sheng Lei; Kin-Fu Chak (Current Microbiology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

A novel lignan glycoside with antioxidant activity from Tinospora sagittata var. yunnanensis - Xiang-Zhong Huang; Chun-Mei Cheng; Yun Dai; Guang-Miao Fu; Jun-Ming Guo; Hui Liang; Chao Wang (Natural Product Research, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Effect of feeding on the function and structure of the digestive system in juvenile southern catfish (Silurus meridionalis Chen) - Ling-Qing Zeng; Feng-Jie Li; Shi-Jian Fu; Zhen-Dong Cao; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2012)

Leaf traits and relationships differ with season as well as among species groupings in a managed Southeastern China forest landscape - Fu-Sheng Chen; Karl J. Niklas; Guang-Sheng Chen; Dali Guo (Plant Ecology, 2012)

Biosorption of zinc and copper from aqueous solutions by two freshwater green microalgae Chlorella pyrenoidosa and Scenedesmus obliquus - Guang-Jie Zhou; Fu-Qiang Peng; Li-Juan Zhang; Guang-Guo Ying (Environmental Science and Pollution Research, 2012)

Evidence of iron cyanides as supplementary nitrogen source to rice seedlings - Xiao-Zhang Yu; Ping-Ping Shen; Ji-Guang Gu; Yan Zhou; Fu-Zhong Zhang (Ecotoxicology, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Cytology and ultrastructure of interactions between Ustilago esculenta and Zizania latifolia - Jing-Ze Zhang; Fu-Qiang Chu; De-Ping Guo; Kevin D. Hyde; Guang-Lin Xie (Mycological Progress, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Assessment of Recanalization of Chronic Total Occlusions on Left Ventricular Function in Patients With or Without Previous Myocardial Infarction by Real-time Three-Dimensional Echocardiography - Wen-Wei Yue; Feng-Tian Huangfu; Jie Yin; Tao Wang; Guang-Fu Wang; Ru-Yi Jia (Cell Biochemistry and Biophysics, 2012)

Sub-chronic effect of perfluorooctanesulfonate (PFOS) on the balance of type 1 and type 2 cytokine in adult C57BL6 mice - Guang-Hui Dong; Miao-Miao Liu; Da Wang; Li Zheng; Zai-Fu Liang; Yi-He Jin (Archives of Toxicology, 2011)

A new carotenoid glycoside from Rehmannia glutinosa - Guang-Miao Fu; She-Po Shi; Fanny C.F. Ip; Hai-Hong Pang; Nancy Y. Ip (Natural Product Research, 2011)

Delineation of the translocation of colicin E7 across the inner membrane of Escherichia coli - Yuh-Ren Chen; Tsung-Yeh Yang; Guang-Sheng Lei; Lung-JR Lin; Kin-Fu Chak (Archives of Microbiology, 2011)

The origin of spongy texture in minerals of mantle xenoliths from the Western Qinling, central China - Ben-Xun Su; Hong-Fu Zhang; Patrick Asamoah Sakyi; Yue-Heng Yang; Ji-Feng Ying; Yan-Jie Tang; Ke-Zhang Qin; Yan Xiao; Xin-Miao Zhao; Qian Mao; Yu-Guang Ma (Contributions to Mineralogy and Petrology, 2011)

RNA interference targeting CITRON can significantly inhibit the proliferation of hepatocellular carcinoma cells - Yinghui Fu; Jian Huang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular Biology Reports, 2011)

Carbon and nitrogen storage in plant and soil as related to nitrogen and water amendment in a temperate steppe of northern China - Fu-Mei Lü; Xiao-Tao Lü; Wei Liu; Xu Han; Guang-Ming Zhang; De-Liang Kong; Xing-Guo Han (Biology and Fertility of Soils, 2011)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Effect of temperature on excess post-exercise oxygen consumption in juvenile southern catfish (Silurus meridionalis Chen) following exhaustive exercise - Ling-Qing Zeng; Yao-Guang Zhang; Zhen-Dong Cao; Shi-Jian Fu (Fish Physiology and Biochemistry, 2010)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Adaptation of the externally feeding bug Elasmucha necopinata (Hemiptera: Acanthosomatidae) to its fig host - Guang-Chang Ma; Hao-Yuan Hu; Li-Ming Niu; Yue-Guan Fu; Zheng-Qiang Peng; Wen-Jun Bu; Da-Wei Huang (Symbiosis, 2009)

Isolation and characterization of polymorphic microsatellite markers in the yellow catfish, Pelteobagrus fulvidraco - Guang-Fu Hu; Hong-Wei Liang; Zhong Li; Chang-Zhong Wang; Qin-Chao Wu; Xiang-Jiang Liu; Xiang-Zhong Luo; Gui-Wei Zou (Conservation Genetics Resources, 2009)

Effect of UV-B radiation on the growth and antioxidant enzymes of Antarctic sea ice microalgae Chlamydomonas sp. ICE-L - Quan-fu Wang; Yan-hua Hou; Jin-lai Miao; Guang-you Li (Acta Physiologiae Plantarum, 2009)

Comparative Tolerances of Various Beauveria bassiana Isolates to UV-B Irradiation with a Description of a Modeling Method to Assess Lethal Dose - Bao-Fu Huang; Ming-Guang Feng (Mycopathologia, 2009)

Sequence Polymorphism and Evolution of Three Cetacean MHC Genes - Shi Xia Xu; Wen Hua Ren; Shu Zhen Li; Fu Wen Wei; Kai Ya Zhou; Guang Yang (Journal of Molecular Evolution, 2009)

Threatened fishes of the world: Schizothorax (Schizopyge) biddulphi Günther, 1876 (Cyprinidae) - Xiang Jiang Liu; Guang Fu Hu (Environmental Biology of Fishes, 2009)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Molecular cloning and characterization of a novel transcript variant of Mtsarg1 gene - Li Li; Gang Liu; Jun-Jiang Fu; Lu-Yun Li; Xiao-Jun Tan; Sheng Yang; Guang-Xiu Lu (Molecular Biology Reports, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Research on the Components of Dust Fall in Hohhot in Comparison with Surface Soil Components in Different Lands of Inner Mongolia Plateau - Chun-xing Hai; Chun-shin Yuan; Guang-tong Liu; Xiao-jia Li; Fu Zhang; Xiu-jiang Zhang (Water, Air, & Soil Pollution, 2008)

Free convection from one thermal and solute source in a confined porous medium - Fu-Yun Zhao; Di Liu; Guang-Fa Tang (Transport in Porous Media, 2007)

Purification and characterization of a psychrophilic glutathione reductase from Antarctic ice microalgae Chlamydomonas sp. Strain ICE-L - Yu Ding; Jin-Lai Miao; Quan-Fu Wang; Zhou Zheng; Guang-You Li; Ji-Chang Jian; Zao-He Wu (Polar Biology, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Facial pain induces the alteration of transient receptor potential vanilloid receptor 1 expression in rat trigeminal ganglion - Lei Pei; Chuan-You Lin; Jia-Pei Dai; Guang-Fu Yin (Neuroscience Bulletin, 2007)

High RAPD but no cpDNA sequence variation in the endemic and endangered plant, Heptacodium miconioides Rehd. (Caprifoliaceae) - Hui-Ping Lu; Yue-Wei Cai; Xiao-Yong Chen; Xin Zhang; Yong-Jie Gu; Guang-Fu Zhang (Genetica, 2006)

Prediction of heterosis using QTLs for yield traits in rapeseed (Brassica napus L.) - Jin-Xiong Shen; Ting-Dong Fu; Guang-Sheng Yang; Jin-Xing Tu; Chao-Zhi Ma (Euphytica, 2006)

Molecular validation of multiple allele inheritance for dominant genic male sterility gene in Brassica napus L - Lai-Qiang Song; Ting-Dong Fu; Jin-Xing Tu; Cao-Zhi Ma; Guang-Sheng Yang (Theoretical and Applied Genetics, 2006)

Expression of CspA and GST by an Antarctic psychrophilic bacterium Colwellia sp. NJ341 at near-freezing temperature - Quan-Fu Wang; Jin-Lai Miao; Yan-Hua Hou; Yu Ding; Guang-You Li (World Journal of Microbiology and Biotechnology, 2006)

Purification and Characterization of a Cold-active Iron Superoxide Dismutase from a Psychrophilic Bacterium, Marinomonas sp. NJ522 - Zhou Zheng; Ying-Hui Jiang; Jin-Lai Miao; Quan-Fu Wang; Bo-Tao Zhang; Guang-You Li (Biotechnology Letters, 2006)

Purification and Characterization of an Extracellular Cold-Active Serine Protease from the Psychrophilic Bacterium Colwellia sp. NJ341 - Quan-Fu Wang; Jin-Lai Miao; Yan-Hua Hou; Yu Ding; Guo-Dong Wang; Guang-You Li (Biotechnology Letters, 2005)

Relationship between resort life cycle and residents’ perception and attitude - Xiao-zhong Yang; Lin Lu; Guang-sheng Zhang; Song Lu; Guo-fu Xuan (Chinese Geographical Science, 2004)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

Impact of oil field exploitation on eco-environment of the Daqing lakes - Shao-peng Yu; Jin-fu Lu; Guang-you Sun (Chinese Geographical Science, 2003)

Applying PPE model based on raga to classify and evaluate soil grade - Qiang Fu; Tie-guang Lu; Hong Fu (Chinese Geographical Science, 2002)

Platinum-group element geochemistry of the Hongge Fe–V–Ti deposit in the Pan-Xi area, southwestern China - Hong Zhong; Xin-Hua Zhou; Mei-Fu Zhou; Min Sun; Bing-Guang Liu (Mineralium Deposita, 2002)

Concept, distribution law and formation machanism of inland saline-alkaline wetland - Guang-you Sun; Xin-zheng Luo; Fu-ke Yi; Xiao-ping Zhang (Chinese Geographical Science, 2000)